1971
DOI: 10.1122/1.549207
|View full text |Cite
|
Sign up to set email alerts
|

Polymer Melt Flow Instabilities in Extrusion: Investigation of the Mechanism and Material and Geometric Variables

Abstract: A comprehensive study of the effect of material, geometric, and operating variables on the onset of melt flow instabilities in extrusion was made. Primary objectives were to compare such melt instabilities for a variety of materials and to correlate instability criteria with independent rheological parameters. Seven polymer melts were studied: two polyethylenes, polypropylene, polystyrene, two polybutadienes, and an SBR copolymer. Two distinct extrusion apparatuses were used: a die fed by a screw extruder syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
22
0

Year Published

1974
1974
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(26 citation statements)
references
References 0 publications
4
22
0
Order By: Relevance
“…It has also been observed that the sharkskin effect is more pronounced in short capillaries of small diameter (Ballenger et al 1971). It can be seen from Fig.…”
supporting
confidence: 52%
“…It has also been observed that the sharkskin effect is more pronounced in short capillaries of small diameter (Ballenger et al 1971). It can be seen from Fig.…”
supporting
confidence: 52%
“…In other words, it seems that there is no attenuation of the instability along the capillary, what was first reported by Bergem [24] using flow visualizations. Consequently, we may imagine that the attenuation of the instability for long capillaries, largely cited in the literature [3,7,8,20] could be a visual artifact: as the pitch is higher, the extrudate looks much less distorted, even if the volume affected by the instability is larger.…”
Section: Characterization Of the Helical Defectmentioning
confidence: 98%
“…Critical parameters usually used to quantify the onset of the upstream instability are mostly shear flow parameters, such as apparent shear rate or wall shear stress. According to Ballenger et al [8], volume defects occur for a critical wall shear stress around 0.1 MPa. However, this critical stress depends on the die length, the temperature and also the molecular weight [9].…”
Section: Introductionmentioning
confidence: 98%
“…5 are for PAA 0.8 % solution and the dextrose syrup respectively and for the exit channel width of 3 mm. As [5] and [6] show clearly effects of viscoelasticity on flow pattern become more pronounced when the exit channel is narrow in width. Observed flow directions are shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The flow field shows no circulating secondary flow and the bending of stream lines are more gradual than the viscoelastic flows in [1J- [3]. Flows [5] and [6] in Fig. 5 are for PAA 0.8 % solution and the dextrose syrup respectively and for the exit channel width of 3 mm.…”
Section: Methodsmentioning
confidence: 99%